2005
DOI: 10.1038/sj.ejcn.1602324
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and associated lifestyles in preconception, pregnancy and postpartum

Abstract: Objective: To identify dietary patterns in women who are planning immediate pregnancy in preconception, weeks 6, 10, 26 and 38 of pregnancy, and 6 months postpartum, and to describe how particular lifestyles, the body mass index (BMI) and sociodemographic factors are associated to these patterns. Design: Longitudinal study throughout the reproductive cycle of food consumption carried out in a Spanish Mediterranean city. Setting: Faculty of Medicine and Health Sciences, Rovira i Virgili University. Subjects: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
211
10
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(249 citation statements)
references
References 34 publications
(45 reference statements)
17
211
10
8
Order By: Relevance
“…The dietary intake was assessed in week 25 of gestation, and intake in the previous 4 weeks was recorded. Cuco et al (2006) found that food intake at one point in pregnancy reflects well the dietary patterns throughout pregnancy, and thus we find it reasonable to assume that the dietary intake does not change substantially. Furthermore, the FFQ has been validated with respect to intake of fruits and vegetables showing that the data recorded in the FFQ are applicable to analyses on food group level , which provide the basis for the construction of the dietary patterns defined in this study.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The dietary intake was assessed in week 25 of gestation, and intake in the previous 4 weeks was recorded. Cuco et al (2006) found that food intake at one point in pregnancy reflects well the dietary patterns throughout pregnancy, and thus we find it reasonable to assume that the dietary intake does not change substantially. Furthermore, the FFQ has been validated with respect to intake of fruits and vegetables showing that the data recorded in the FFQ are applicable to analyses on food group level , which provide the basis for the construction of the dietary patterns defined in this study.…”
Section: Discussionmentioning
confidence: 63%
“…Factor analysis has been employed in analysis of diet during pregnancy in a Spanish study (Cuco et al, 2006), where diet at different time points in pregnancy in relation to lifestyle factors was examined, and in a Mexican-American survey (Wolff and Wolff, 1995), where association between dietary patterns in pregnancy and birth weight was investigated. As the human diet consists of a large variety of nutrients, and intakes of these will often correlate, it may be appropriate to analyse dietary patterns as an alternative to examining a potential effect of intakes of single nutrients on health outcome.…”
Section: Introductionmentioning
confidence: 99%
“….0-34.9, and Q35.0 kg/m 2 ) RR3 adjusted for age (5-year category), parity (0, 1, 2, 3+), BMI (nine categories), race/ethnicity, cigarette smoking status (never, past, current), family history of diabetes in a first-degree relative (yes, no), alcohol intake (0, 0.1-5.0, 5.1-15.0 or >15 g/day), physical activity (quintile), and total energy (quintile) Dietary information during pregnancy was not specifically measured in the current study. However, limited data suggest that dietary patterns and macronutrient intakes do not vary significantly between periods prior to conception and periods of pregnancy [49], although women generally increase their energy intake in pregnancy to meet fetal need. It is plausible that much of the adverse effects of red meat and processed meat on the risk of GDM that we observed for the pregravid period reflected continued consumption patterns during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary patterns rich in vitamins, minerals and proteins are associated with higher birth weight 13 . Older women with a higher level of education are more likely to follow a healthy diet and prevalence of pregestational overweight is lower in this group 8,12,14 . It has also been shown that increased parity, prepregnancy maternal overweight, being single and unemployed and smoking are factors associated with unhealthy dietary patterns during pregnancy 12,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, pregnant women pay more attention to diet and food choices than nonpregnant women 9 ; thus pregnancy is an ideal time to make changes to dietary habits 10 . Dietary patterns during pregnancy have been associated with nutritional intake, sociodemographic characteristics and outcomes for babies 8,11,12,13,14,15 . Dietary patterns rich in vitamins, minerals and proteins are associated with higher birth weight 13 .…”
Section: Introductionmentioning
confidence: 99%